ANALISIS PENGARUH RISIKO SISTEMATIS DAN LIKUIDITAS TERHADAP TINGKAT PENGEMBALIAN SAHAM DALAM PERUSAHAAN NON-KEUANGAN LQ-45 PERIODE 2007-2009 - Sumani .; Suhari . (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
This study aims to examine how the effect of systematic risk and liquidity on stock returns. In this study, researchers found that the systematic risk and liquidity influence stock returns of the shares. Researchers focused on non-financial companies listed in the LQ-45 index for the period 2007 to 2009. The method used is panel data and a sample of 11 non-financial firms. For statistical processing methods used least squares regression analysis. Researchers found that the the returns on shares of non financial companies listed in the LQ-45 index, are simultaneously affected by systematic risk and liquidity. Results of studies have shown that there is significant influence between systematic risk and the liquidity of the stock returns in the fixed effect models, but there are also other factors beyond the systematic risk and liquidity that also influence the rate of return on stocks.Key words: systematic risk, liquidity of shares, bid-ask spread, rate of return